The Leading Economic Sector in Samarinda - Ilham Abu; Nasib Subagio; Sutrisno Sutrisno (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Economic growth can be influenced by the economic sector. To increase the economic growth of a region, it is necessary to determine the leading economic sector so that it can encourage the development of other sectors based on the business field. This study aims to determine the leading and non-leading economic sectors that provide a contribution to the economy of Samarinda. In this study, the researchers applied a quantitative study and utilized secondary data gained from the Central Statistics Agency. Data in this study were data concerning the PDRB of Samarinda and East Kalimantan in 2020. The employed data analysis was the Location Quotient (LQ) method utilizing the Microsoft Excel application. Results indicate that the leading economic sectors that have a large contribution to the economy of Samarinda are financial services and insurance with a contribution of 4.84%, while the non-leading economic sectors are agriculture, forestry, fisheries, mining, and quarrying, in which processing industries possess a contribution less than 1 to the economy of Samarinda.